Offending, crime and justice survey, 2003 (Offending, Crime and Justice Survey, 2008)
The Offending, Crime and Justice Survey (OCJS) (also sometimes known as the Crime and Justice Survey), was the first national longitudinal, self-report offending survey for England and Wales. The series began in 2003, the initial survey representing the first wave in a planned four-year rotating panel study, and ended with the 2006 wave. A longitudinal dataset based on the four years of the study was released in 2009 (held at the Archive under SN 6345). The OCJS was commissioned by the Home Office, with the overall objective of providing a solid base for measuring the prevalence of offending and drug use in the general population of England and Wales. The survey was developed in response to a significant gap in data on offending in the general population, as opposed to particular groups such as convicted offenders. A specific aim of the series was to monitor trends in offending among young people. The OCJS series was designed as a 'rotating panel' which means that in each subsequent year, part of the previous year's sample was re-interviewed, and was augmented by a further 'fresh' sample to ensure a cross-sectional representative sample of young people. The aim of this design was to fulfil two objectives: firstly, to provide a solid cross-sectional base from which to monitor year-on-year measures of offending, drug use, and contact with the CJS over the four-year tracking period (2003-2006); and secondly, to provide longitudinal insight into individual behaviour and attitudinal changes over time, and to enable the Home Office to identify temporal links between and within the key survey measures. The OCJS was managed by a team of researchers in the Home Office Research, Development and Statistics Directorate. The Home Office commissioned BMRB Social Research and the National Centre for Social Research (NatCen) to conduct the surveys jointly. Both organisations were involved in developing the surveys and, at each wave, the fieldwork was split between the two agencies. OCJS 2003: The OCJS 2003 was the first survey in the series, and was conducted between January and July 2003, with a sample of around 12,000 people aged 10-65 years, living in private households in England and Wales. The survey collected information on the extent and nature of offending behaviour, drug and alcohol use, attitudes to and contact with the criminal justice system and experiences of victimisation. Respondents were asked about offending behaviour in their lifetime, and during the last 12 months. The main aims of the OCJS 2003 were to provide: a measure of the number of offenders in the general household population in England and Wales and the offences they commit, including those who will not have been processed by the criminal justice system; an estimate of the proportion of offenders and offences that come to the attention of criminal justice agencies; an estimate of the proportion of offenders who are young people and the proportion of crime they commit; information on the nature of offences committed, and in particular, offender motivations; information on patterns of drug use and links to offending; data to identify risk factors associated with the onset and continuation of offending and drug use, and factors associated with desistance. For the third edition (August 2008), an updated version of the main file has been deposited. Derived variables relating to the number of times that respondents have offended in the past year have been revised due to an improvement in the method of imputing values for those who refused to answer the count of offending questions. New users should also note that the domestic violence data were removed at an earlier edition due to concerns over consistency.